First record of the non-native species Bryconops aff. melanurus (Bloch, 1794) (Characiformes: Iguanodectidae) in the Paraná River floodplain, upper Paraná River basin, Brazil - dos Reis, Renan B.; Roloff, Matheus Zirondi; Pedroso, Thiago Henrique; Reinas, Gabriela Cassia Zanon; Stabile, Bruno Henrique Mioto; Martins, Isadora Carolina; Carvalho, Fernando R. [UNESP] (Wiley, 2025)
This study presents the first record of the non-native species Bryconops aff. melanurus (Bloch 1794) within the upper Paraná River floodplain in Brazil. Two specimens were collected in December 2023 as part of a long-term ecological research programme (PELD). A morphological analysis confirmed species identity. The introduction of B. aff. melanurus into this region raises concerns about its potential impact on the local ichthyofauna because of its dietary plasticity and the disturbed nature of the ecoregion. It is essential to conduct continuous monitoring to assess the ecological implications of the introduction.
Keywords: fishes taxonomy; ichthyofauna inventory; long-term ecological programme (PELD site 6); species introduction; subgenus Creatochanes